Ultrasonic Pretreatment-Assisted Electrohydrodynamic Drying of Potato Slices - Zhiyuan Cao; Changjiang Ding; Rui Zhao; Zhiqing Song; Hao Chen (Journal of Food Quality)
To investigate the drying characteristics and mechanism during electrohydrodynamic (EHD) drying with ultrasonic pretreatment, the ultrasonic pretreatment-assisted EHD drying method at different power values was used to carry out the drying experiment of potatoes. To carry out this study, potato slices were pretreated with different ultrasonic power values (150, 180, 210, 240, and 270 W) or without ultrasound for 30 min at 30°C. The corresponding voltage was 18 kV during EHD drying. The moisture ratio, drying rate, color, shrinkage, and rehydration rate of potatoes were determined. The microstructure of potatoes was analyzed using infrared spectroscopy and scanning electron microscopy. Eight mathematical models were used to fit the drying of potatoes. Results showed that, compared with the control group, the ultrasonic pretreatment combined with the EHD drying group had improved the drying rate of potato slices, which was different at varying ultrasonic power values. Ultrasonic pretreatment had a remarkable effect on the color of the potato but had little effect on the shrinkage rate. The maximum rehydration rate is 5.7704 at 180 W. The minimum and maximum values of effective moisture diffusivity (Deff) were 3.4070 × 10−7 m2/s and 4.1160 × 10−7 m2/s, respectively. The effect of ultrasonic power pretreatment on the microstructure of potato in the EHD drying process was significant (p>0.05). According to the statistical parameter evaluation, eight mathematical models could satisfactorily describe drying curves of potato slices dried under EHD with ultrasonic pretreatment, and the logarithmic model was best suited. This work provides a theoretical basis and practical guidance to further understand the parameter characteristics and mechanism of ultrasonic pretreatment combined with the EHD drying technology.